Lead-free solid state mechanochemical synthesis of Cs2NaBi1-XFeXCl6 double perovskite: reduces band gap and enhances optical properties - Udavant, Rohini; Thawarkar, Sachin; Rondiya, Sachin; Shelke, Ankita; Aher, Rahul; Ajithkumar, Thalasseril G.; Cross, Russell W.; Dzade, Nelson Y.; Jadkar, Sandesh (Inorganic Chemistry, 2023)
Efficient and stable lead-free halide double perovskites (DPs) have attracted great attention for the future generation of electronic devices. Herein, we have developed a doping approach to incorporate Fe3+ ions into the Cs2NaBiCl6 crystal unit and reveal a crystallographic and optoelectronic study of the Cs2NaBi1-xFexCl6 double perovskite. We report a simple solid-state mechanochemical method that has a solvent-free, one-step, green chemistry approach for the synthesis of Cs2NaBi1-xFexCl6 phosphor. The analysis of powder X-ray diffraction (XRD) data determines the contraction of the lattice due to the incorporation of Fe3+ cations, and this effect is well supported by X-ray photoelectron spectroscopy (XPS), field emission scanning electron microscopy (FE-SEM), Raman spectroscopy, and solid-state nuclear magnetic resonance spectroscopy (ss-NMR). The band gap is reduced with increasing Fe content owing to the strong overlap of the Fe-3d orbitals with Cl-3p orbitals and shift of the valence band maxima (VBM) toward higher energies, as confirmed by ultraviolet photoelectron spectroscopy (UPS) and density functional theory (DFT) analyses. Photoluminescence (PL) studies of Cs2NaBi1-xFexCl6 phosphors exhibit a large Stokes shift, broadband emission, and increased PL intensity more than ten times for 15% of Fe content phosphor with enhancement in the average decay lifetimes (up to 38 ns) compared to pristine Cs2NaBiCl6 DP. These results indicate that the transition of dark self-trapping of excitons (STEs) into bright STEs enhances yellow emission. XRD, UV, and thermo-gravimetric analysis (TGA) confirmed that the Cs2NaB1-xFexCl6 DPs have good structural and thermal stabilities. Our findings indicate that the doping of Fe3+ cations into the Cs2NaBiCl6 lattice is a constructive strategy to enhance significantly the optoelectronic properties of these phosphors.